EPEN-44. EXTRACELLULAR VESICLES OF SUPRATENTORIAL EPENDYMOMA RELA MEDIATE INTERACTIONS WITH CELLS OF THE TUMOR MICROENVIRONMENT - Maass, Kendra K (Neuro Oncol, 2020)
Ependymal tumors (EPNs) account for ~10% of all pediatric brain tumors. Supratentorial EPN characterized by RELA fusions (ST-EPN-RELA) and posterior fossa EPN group A (PF-EPN-A) form the two most frequent molecular groups, both of which are associated with poor prognosis and for which only limited therapeutic options are available. Since pediatric EPNs have a relatively low mutational burden, identification and characterization of tumor-associated pathways and molecular processes is of critical importance to inform potential therapeutic targets. Previous transcriptional studies implicated aberrant vesicular pathways in ST-EPN-RELA, prompting further investigation into their putative role in EPN pathogenesis. To this aim, we isolated extracellular vesicles (EVs) of ST-EPN-RELA patient derived cell lines and performed protein mass spectrometry. The specific ST-EPN-RELA EV protein content resembles the parental cells as well as primary tumors. Promising candidates to be transferred by ST-EPN-RELA EVs but not control EVs were associated with unfolded protein response and endoplasmic reticulum stress. When uptaken by recipient cells of the tumor microenvironment, brain endothelial cells or microglia, ST-EPN-RELA EVs induced proliferation and had a chemoattractant effect towards the tumor. ST-EPN-RELA EVs stimulated angiogenesis of brain endothelial cells potentially by the transfer of ER stress proteins. Uptake of ST-EPN-RELA EVs by microglia changed their activation status indicating a tumor promoting function through EV transfer. Therefore, we hypothesize that vesicular pathways play an important role in the pathogenesis of pediatric ST-EPN-RELAs and that an improved understanding may promote new therapeutic opportunities.